Elizabeth Sinkler Coxe's tales from the grand tour, 1890-1910 - Coxe, Elizabeth Sinkler, 1843-1919; LeClercq, Anne Sinkler Whaley, 1942- (Women's diaries and letters of the South., 2006)
"Elizabeth Sinkler Coxe's Tales from the Grand Tour, 1890-1910 is a travelogue of captivating adventures through exotic lands as experienced by an intrepid American aristocrat and her son at the dawn of the twentieth century."